ANXIETY OF WINSTON SMITH IN GEORGE ORWELL'S 1984:A PSYCHOANALYTIC APPROACH - PRIBADI, SUSILO (2007)
The problem of this study is how the anxiety of the major character is reflected in George Orwell's 1984. The objectives of this study are to analyze George Orwell's 1984 based on the structural elements and to analyze the novel based on the psychoanalytic approach. The writer employs qualitative method. In this method the writer uses two data sources, namely primary and secondary data sources. The primary data source is the novel itself. The secondary data sources are internet and other sources, which are related to the analysis. The method of data collection is library research and the technique is descriptive technique. Based on the analysis, the writer draws some conclusions as follows. First, anxiety as the effect of the conflicts of the elements of personality changes person to do unusual thing. It changes the personality. The second, anxiety may influence someone to be courageous. The courage appears when the person is pressed by something he or she dislikes.